PENGEMBANGAN SOAL MATEMATIKA HOTS (HIGHER ORDER THINKING SKILLS) SMA ALA TAKSONOMI KRULIK & RUDNICK - Widodo, Suryo; Katminingsih, Yuni; Nurwiani, Nurwiani (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2021)
The lack of availability of HOTS math questions in the field makes it difficult for teachers to teach students higher order thinking skills. Most of the hots questions developed were based on Bloom's taxonomy revised by Anderson et al. This study aims to produce valid and reliable HOTS questions and to measure students' higher-order thinking skills. This study uses a Tessmer model development research. This development model consists of 2 stages, namely (1) the preliminary stage and (2) the formative evaluation. Instrument testing was carried out in class X MIPA E SMA Negeri 1 Kediri. The data collection instruments included a question grid, a HOTS class X maths question sheet based on Krulik-Rudnick's, a validation sheet, and a question readability questionnaire. The data analysis technique uses item analysis which consists of validity, reliability, level of difficulty, and distinguishing power. This research has produced 11 items that are valid, practical, and reliable. In addition, this study produced a reliable item with a Cronbach's Alpha value of 0.921. The results of the test questions concluded that the high-order thinking skills (HOTS) of class X students in mathematics were good with an average score of 33.17.